The effect of PAMAM dendrimer concentration, generation size and surface functional group on the aqueous solubility of candesartan cilexetil - Erturk, Ali Serol; Gurbuz, Mustafa Ulvi; Tulu, Metin (TAYLOR & FRANCIS LTD, 2017)
This article investigates the aqueous solubility of the poorly soluble drug candesartan cilexetil (CC) in the presence of poly(amidoamine) (PAMAM) dendrimers. The effect of variables such as concentration, generation size (G2-G4), and surface groups (NH2, COOH and TRIS) of PAMAMs on the aqueous solubility of CC was studied. A two-factor factorial (3x3) ANOVA design was used to study the effect of generation size and surface functional group of the PAMAMs. The results showed that the aqueous solubility of CC in the presence of carboxyl and TRIS-terminated PAMAMs was higher than those of amine-terminated PAMAMs, and the effect of surface functional group of the PAMAMs on the aqueous solubility of CC was dependent on the generation size (p G3.COOH (3456)>G4.TRIS (2362)>G2.COOH (1013)>G3.TRIS (749)>G2.TRIS (293)>G4.NH2 (91)>G3.NH2 (50)>G2.NH2 (37). The CC-PAMAM dendrimer inclusion complexes were characterized by UV-Vis, attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) and differential thermal analysis (DTA) techniques. Regarding the results of these techniques, improvement in the solubility of CC is expected primarily through the intermolecular hydrogen bonding between the drug and internal tertiary and surface functional groups of the studied PAMAMs.
Keywords: PAMAM dendrimers; solubilization; candesartan cilexetil; inclusion complex; MICROWAVE-ASSISTED SYNTHESIS; POLY(AMIDOAMINE) DENDRIMERS; POLY(AMIDO)AMINE DENDRIMERS; DRUG-DELIVERY; BIOMEDICAL APPLICATIONS; LIPID-MEMBRANES; SOLID-STATE; IN-VITRO; BIOAVAILABILITY; ENHANCEMENT; Pharmacology & Pharmacy